High concentrations of plasma trimethylamine-n-oxide is associated with long-term cardiovascular mortality in patients with acute coronary syndrome. (14th October 2021) - Eyileten, C; Jarosz-Popek, J; Jakubik, D; Wolska, M; Fitas, A; Czajka, P; Nowak, A; Ufnal, M; Postula, M; Toma, A; Lang, I; Siller-Matula, J M; et al.
Abstract: Background: Acute coronary syndrome (ACS) remains a leading cause of mortality worldwide [1]. Patients who experienced ACS are at high risk of future cardiovascular events and death [2–4]. Identification of reliable predictive tools could potentially improve the risk stratification [5]. Numerous studies revealed that intestinal microbial organisms (microbiota) and its metabolites, as TMAO (trimethylamine-N-oxide) may play a pathogenic role in a cardiovascular disease (CVD) and ACS [6]. Elevated concentration of circulating TMAO has been associated with increased risk of CVD and major adverse cardiac events (MACE), including myocardial infarction (MI), stroke, major bleeding and all-cause mortality [7]. Purpose: To investigate the association of liver metabolite TMAO with cardiovascular disease (CV)-related and all-cause mortality in patients with acute coronary syndrome (ACS) who underwent percutaneous coronary intervention. Methods: Our prospective observational study enrolled 292 patients with ACS. Plasma concentrations of TMAO were measured during the hospitalization for ACS. Observation period lasted 7 years in the median. Adjusted Cox-regression analysis was used for prediction of mortality. Results: ROC curve analysis revealed that increasing concentrations of TMAO levels assessed at the time point of ACS significantly predicted the risk of CV mortality (c-index=0.78, p<0.001). The cut-off value of >4 μmol/L, labeled as high TMAO level (23% of study population), provided the greatest sum of sensitivity (85%) and specificity (80%) for the prediction of CV mortality and was associated with a positive predictive value of 16% and a negative predictive value of 99%. A multivariate Cox regression model revealed that high TMAO level was a strong and independent predictor of CV death (HR=11.62, 95% CI: 2.26–59.67; p=0.003). High TMAO levels as compared with low TMAO levels were associated with the highest risk of CV death in a subpopulation of patients with diabetes mellitus (27.3% vs 2.6%; p=0.004). Although increasing TMAO levels were also significantly associated with all-cause mortality, their estimates for diagnostic accuracy were low. Conclusions: High TMAO level is a strong and independent predictor of long-term CV mortality among patients presenting with ACS. TMAO concentration of 4 μmol/L may be a cut-off value for prognosis of ACS patients. FUNDunding Acknowledgement: Type of funding sources: None.